Nocturnal seizures are associated with more severe hypoxemia and increased risk of postictal generalized EEG suppression. (17th July 2017) - Latreille, Véronique; Abdennadher, Myriam; Dworetzky, Barbara A.; Ramel, Judith; White, David; Katz, Eliot; Zarowski, Marcin; Kothare, Sanjeev; Pavlova, Milena
Summary: Patients with epilepsy have 20‐fold risk of sudden death when compared to the general population. Uncontrolled seizures is the most consistent risk factor, and death often occurs at night or in relation to sleep. We examined seizure‐related respiratory disturbances in sleep versus wakefulness, focusing on periictal oxygen saturation. Respiratory measures were examined in 48 recorded seizures (sleep, n = 23, wake, n = 25) from 20 adult patients with epilepsy. Seizures from sleep were associated with lower saturation, as compared to seizures from wakefulness, both during ictal (sleep median = 90.8, wake median = 95.5; p < 0.01) and postictal periods (sleep median = 94.3, wake median = 96.9; p = 0.05). Compared to wake‐related seizures, seizures from sleep were also associated with a larger desaturation drop (sleep median = −4.2, wake median = −1.2; p = 0.01). Postictal generalized electroencephalography (EEG) suppression (PGES) occurred more frequently after seizures from sleep (39%), as compared to wake‐related seizures (8%, p = 0.01). Our findings suggest that nocturnal seizures may entail a higher sudden unexpected death in epilepsy (SUDEP) severity burden, as they are associated with more severe and longer hypoxemia events, and more frequently followed by PGES, both factors implicated in sudden death.